2021
DOI: 10.1007/s00704-021-03580-6
|View full text |Cite
|
Sign up to set email alerts
|

Applying urban climate model in prediction mode—evaluation of MUKLIMO_3 model performance for Austrian cities based on the summer period of 2019

Abstract: Extreme heat events are natural hazards affecting many regions of the world. This study uses an example of the six largest cities in Austria to demonstrate the potential of urban climate model simulations applied in prediction mode providing detailed information on thermal conditions. For this purpose, the urban climate model MUKLIMO_3 of the German Meteorological Service (DWD) coupled with the hydrostatic numerical weather prediction model, ALARO, is used to simulate the development of the urban heat island (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In particular, days without cold air advection or precipitation and with little wind, which generally lead to the strongest heat stress during heatwaves, can be modelled realistically with MUKLIMO_3. However, days with changes in mesoscale background conditions during the simulation period lead to larger biases between modelled and measured air temperatures, which is also detected by Hollósi et al [20]. Compared to Bokwa et al [3], this study found lower Pearson correlation values between measured and modelled air temperatures.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In particular, days without cold air advection or precipitation and with little wind, which generally lead to the strongest heat stress during heatwaves, can be modelled realistically with MUKLIMO_3. However, days with changes in mesoscale background conditions during the simulation period lead to larger biases between modelled and measured air temperatures, which is also detected by Hollósi et al [20]. Compared to Bokwa et al [3], this study found lower Pearson correlation values between measured and modelled air temperatures.…”
Section: Discussionsupporting
confidence: 48%
“…Changes in meteorological conditions during the model run can thus not be captured by the model. Hollósi et al [20] mention that a positive or negative cloud cover bias highly influences the diurnal ranges of air temperature and relative humidity and could show that excluding simulations of cloud cover bias of more than 50 % improve the air temperature results by about 10 %.…”
Section: Model Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The applications of the model are various: estimating the effect of urbanization (Žuvela‐Aloise et al ., 2014), effect of roof albedo modifications (Žuvela‐Aloise et al ., 2018), implementation of blue and green infrastructure (Žuvela‐Aloise et al ., 2016; Geletič et al ., 2020), and estimations of heat load in a future climate (Früh et al ., 2011; Geletič et al ., 2019a; Oswald et al ., 2020; Schau‐Noppel et al ., 2020). It was also successfully used in a prediction mode for Austrian cities (Hollósi et al ., 2021).…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…[8,9]), numerical urban climate model simulations (e.g. [10,11]), or analyses based on self-designed urban air temperature measurement networks (e.g. [12][13][14]).…”
Section: Introductionmentioning
confidence: 99%